Hospital Costs and Excess Bed Capacity: A Statistical Analysis - Keeler, Theodore E.; Ying, John S. (The Review of Economics and Statistics, 1996)
This paper develops and estimates a cost model for U.S. hospitals, analyzing the cost of excess bed capacity. A new estimate is worth making for at least two reasons. Recent changes in the economic environment of hospitals have caused their utilization rates to fall sharply, making previous estimates inaccurate. Second, we employ econometric techniques not previously applied to this problem, with estimation based on all short-term community hospitals from 1979-89. Our results, based on conservative estimates of the average optimal occupancy rate, indicate an annual cost of excess bed capacity of $17.2 billion in 1989, $24.1 billion in 1991, and over $25 billion in 1993. Copyright 1996 by MIT Press.